2021
DOI: 10.1007/s10566-021-09640-2
|View full text |Cite
|
Sign up to set email alerts
|

Bullying in Students with Special Education Needs and Learning Difficulties: The Role of the Student–Teacher Relationship Quality and Students’ Social Status in the Peer Group

Abstract: Background Children with Special Education Needs and Learning Difficulties are at risk of being excluded, or bullied because of their impairments. Within the bullying literature, two variables have been shown to be key in terms of its predictions: student–teacher relationship and students’ social status among peers. Objective The aim of this research was to assess the association between the student–teacher relationship and students’ social status in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…Regarding feeling experience between bullying exposed deaf and dumbed students, the current study found that slightly less than one third and one third of studied students reported feelings of depression and anger respectively. These were consistent with Cosma et al, 2017 (39) who showed that youth who have been bullied were more likely to report lower levels of confidence and happiness and higher levels of psychological symptoms. Regarding time of exposure to bullying, the current study found that more than one quarter of bullying exposed deaf and dump students were bullied every day.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding feeling experience between bullying exposed deaf and dumbed students, the current study found that slightly less than one third and one third of studied students reported feelings of depression and anger respectively. These were consistent with Cosma et al, 2017 (39) who showed that youth who have been bullied were more likely to report lower levels of confidence and happiness and higher levels of psychological symptoms. Regarding time of exposure to bullying, the current study found that more than one quarter of bullying exposed deaf and dump students were bullied every day.…”
Section: Discussionsupporting
confidence: 91%
“…Some researchers have defined student violence as patterns of offensive, coercive behaviour against others that include physical abuse, psychological abuse, economic exploitation, or property destruction carried out by some students against their colleagues, teachers, or attacks on university laws and property (Berchiatti et al, 2021). The school stage is a crucial stage for young people in terms of looking forward to the future of their professional and family life, in which they set goals and strive to achieve them in a changing, socially, economically, and politically volatile world.…”
Section: Literature Reviewmentioning
confidence: 99%